Development and Characterization of Soy Protein Isolate/Xylose Film - Mingqiao Chen; Qinghua Yuan; Zhidan Lin (International Journal of Polymer Science)
This paper used different concentrations of xylose as a cross-linker to initiate the Maillard reaction with the soy protein isolate matrix. The mechanical performance and moisture resistance of the soy protein isolate film were enhanced. Measuring the specific wavelength absorbance, free amino group concentration, and fluorescence spectrum of the cross-linked result revealed the alteration of the soy protein isolate. Simultaneously, composite films made by crosslinking soy protein isolate with xylose were thoroughly investigated. Mechanical properties, contact angle measurement, water vapour transmission rate, optical properties, and thermal performance were used to determine the film’s fundamental properties, and the interaction relationship between soy protein isolate, xylose, and glycerol was studied using infrared spectroscopy. The study found that the modified SPI film outperformed the unmodified film, particularly when the xylose content was 20%. The tensile strength reached 6.26 MPa, and the water vapour permeability was reduced to 5.45×10−8 g·mm/m2·s·Pa. It also exhibited excellent UV resistance and good thermal stability.